Penyuluhan Kecerdasan Emosional Dalam Mencegah Kenakalan Remaja Pada Siswa Di SMA Negeri 6 Kota Bengkulu - Delfina, Rina; Sardaniah, Sardaniah (Utami Publisher, 2025)
Adolescence is a challenging developmental stage, marked by significant emotional, social, and psychological changes. In this phase, adolescents are vulnerable to deviant behavior or juvenile delinquency due to lack of self-control and environmental influences. Emotional intelligence, which includes the ability to recognize, understand, and manage one's own emotions and those of others, is believed to play an important role in shaping positive behavior in adolescents. Community service aims to increase adolescents' knowledge about emotional intelligence in preventing juvenile delinquency. The method used in this community service is in the form of counseling on emotional intelligence and juvenile delinquency. The importance of emotional intelligence in adolescents is because adolescents with high levels of emotional intelligence tend to have better self-control, empathy for others, and are able to make wise decisions in complex social situations. The target of this community service activity is students at SMA Negeri 6 Kota Bengkulu. Developing emotional intelligence from an early age is an effective preventive strategy in reducing the risk of juvenile delinquency and forming emotionally healthy characters.